Efektivitas Digital Learning Materials (DLMs) Terhadap Peningkatan Motivasi Mahasiswa Keperawatan Tentang Rawat Luka Pada Masa Pandemik Covid-19 - Yuni Kurniawaty (Universitas Malahayati Lampung, 2022)
ABSTRACT The COVID-19 pandemic situation requires us to choose to learn using the Digital Learning Materials (DLMs) model. The purpose of the study was to analyze the effectiveness of DLMs in increasing the motivation of nursing students about wound care during the covid-19 pandemic. The research design was a quasi-experimental post-test with a control group design. The research was conducted online from the residence of each respondent from August 2021 – to January 2022. The research population of Nursing Science Study Program students was 79 people. The sampling technique was simple random sampling. The inclusion criteria are as follows: (1) Willing to be a respondent, (2) Committed to participating in a series of research processes, (3) Actively participating in the learning process. Exclusion criteria: Respondents are sick. The sample consisted of two groups, namely the teaching intervention group using the DLMs method with 30 respondents and the control group using the face-to-face conventional method with 30 respondents. The instrument is a Motivation Questionnaire consisting of 10 statements with answer choices strongly agree, agree disagree, and strongly disagree. The validity test has a value 0.05 and all of them are declared valid. The reliability test was indicated by the Cronbach's Alpha value of 0.729, each item of the statement on the motivation questionnaire was declared reliable. The results of the normality test with Kolmogorov Smirnov = 0.586 0.05, it was concluded that the respondent's data was normally distributed. The statistical test used is the Independent sample t-test with = 0.042 0.05, so it can be concluded that there is a significant difference between the motivation in the DLMs learning method group and the face-to-face conventional learning method group with a mean value of DLMs higher than the conventional face-to-face method. The DLMs method for nursing students' wound care is a method that can increase student motivation, which is an important moderator in linking learning methods to student learning performance. It is hoped that the increase in student motivation due to the DLMs learning method can improve student learning performance in studying wound care. Keywords: DLMs, Motivation, Covid-19 ABSTRAK Situasi pandemik COVID-19 mengharuskan kita memilih pembelajaran dengan model Digital Learning Materials (DLMs). Tujuan penelitian adalah menganalisis efektivitas DLMs terhadap peningkatan motivasi mahasiswa keperawatan tentang rawat luka pada masa pandemik covid-19. Desain penelitian quasi eksperiment posttest with control group design. Penelitian dilakukan secara online dari tempat tinggal masing-masing responden pada bulan Agustus 2021 – Januari 2022. Populasi penelitian mahasiswa Prodi Ilmu Keperawatan sejumlah 79 orang. Teknik pengambilan sampel dengan simple random sampling. Kriteria inklusi sebagai berikut: (1) Bersedia menjadi responden, (2) Berkomitmen untuk mengikuti rangkaian proses penelitian, (3) Aktif mengikuti proses pembelajaran. Kriteria eksklusi: Responden dalam keadaan sakit. Sampel terdiri dari dua kelompok yaitu kelompok intervensi pengajaran dengan metode DLMs sebanyak 30 responden dan kelompok kontrol dengan metode konvensional tatap muka sebanyak 30 responden. Instrumen berupa Kuesioner Motivasi yang terdiri dari 10 pernyataan dengan pilihan jawaban sangat setuju, setuju tidak setuju dan sangat tidak setuju. Uji Validitas memiliki nilai 0,05 seluruhnya dinyatakan valid. Uji Reliabilitas ditunjukkan dengan nilai Cronbach's Alpha 0,729 tiap butir pernyataan soal kuesioner motivasi dinyatakan reliable. Hasil uji uji normalitas dengan Kolmogorov Smirnov ρ = 0,586 0,05 disimpulkan data responden berdistribusi normal. Uji statistik yang digunakan adalah Independet sample t test dengan ρ = 0,042 0,05 maka dapat disimpulkan terdapat perbedaan yang signifikan antara motivasi pada kelompok metode pembelajaran DLMs dengan kelompok metode pembelajaran konvensional dengan tatap muka dengan nilai mean DLMs lebih tinggi daripada metode konvensional tatap muka. Metode DLMs rawat luka mahasiswa keperawatan merupakan metode yang mampu meningkatkan motivasi mahasiswa yang menjadi moderator penting menghubungkan metode pembelajaran terhadap kinerja belajar mahasiswa. Diharapkan dengan meningkatnya motivasi mahasiswa akibat metode pembelajaran DLMs mampu meningkatkan kinerja belajar mahasiswa dalam mempelajari rawat luka. Kata Kunci: DLMs, Motivasi, Covid-19